Cipasung Heritage Creative Hub: Innovation In Msme Development Based On Cultural Tourism And Agrotourism In Cipasung Village, Lemahsugih, Majalengka - Akhmad Hidayat Nurul Akbar; Siti Amirah Makarim (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
This community service activity aims to develop the "Cipasung Heritage Creative Hub" model through revitalization of Village-Owned Enterprises (BUMDes) and strengthening the capacity of local Micro, Small, and Medium Enterprises (MSMEs) in Cipasung Village, Lemahsugih District, Majalengka Regency. The village has extraordinary potential in developing creative economy based on cultural tourism and agrotourism, with the presence of tea gardens that have become tourist attractions, bamboo craft traditions that are still preserved, and rich local wisdom. The method used includes a participatory approach involving all village stakeholders, creative economy skills training, development of superior products based on local wisdom, and formation of digital marketing networks. The program was implemented for 12 months involving 150 participants from various community groups, including tea farmers, bamboo craftsmen, women's groups, and village youth. The results showed a significant increase in local MSME capacity, with 85% of participants successfully developing innovative products based on tea and bamboo crafts. The average income of MSMEs increased by 60% within 6 months after program implementation. BUMDes Cipasung successfully integrated tea agrotourism with creative economy, creating educational tourism packages that attracted 2,500 tourists in the first year. The "Cipasung Heritage Creative Hub" model proved effective in preserving local culture while improving community economic welfare.